2014
DOI: 10.1186/1758-5996-6-76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic variability on short term prognosis in acute myocardial infarction subjects undergoing primary percutaneous coronary interventions

Abstract: ObjectiveGlycemic variability (GV) still remains unclear whether acute glycemic excursion has the important prognostic significance in ST-segment elevation myocardial infarction (STEMI) patients undergoing p-PCI. So our aim is to assess the prognostic value of GV in STEMI patients undergoing p-PCI.MethodsWe studied 237 STEMI patients undergoing p-PCI, whose clinical and laboratory data were collected. We used a continuous glucose monitoring system (CGMS) to measure the fluctuations of blood glucose. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…For coefficient of variation as a parameter of glycemic variability comparable results were observed in Verona diabetes study (10) . When MAGE was used as a parameter of GV Zhang J et al (11) and Su G et al (12) observed comparable results. We observed increased proportionate mortality in 3 rd and 4 th quartiles of SD, the results which were consistent with study of Krinsley JS et al (13) .…”
Section: Discussionsupporting
confidence: 63%
“…For coefficient of variation as a parameter of glycemic variability comparable results were observed in Verona diabetes study (10) . When MAGE was used as a parameter of GV Zhang J et al (11) and Su G et al (12) observed comparable results. We observed increased proportionate mortality in 3 rd and 4 th quartiles of SD, the results which were consistent with study of Krinsley JS et al (13) .…”
Section: Discussionsupporting
confidence: 63%
“…Of note, MAGEs ≥3.4 mmol/L was an independent predictor of CAD in this population; indeed, among the independent predictors of Gensini Score, the area under the ROC curve for MAGEs (0.618, P = 0.001) was superior to that for HbA1c (0.554, P = 0.129), indicating that the predictable value of MAGEs was even higher than HbA1c . Furthermore, in a cohort of 237 patients with ST segment elevation MI undergoing PCI, a higher GV was demonstrated to be an independent prognostic factor for composite MACE during in‐hospital and 30‐day follow‐up both for diabetic (OR 2.857, 95% CI 1.143‐7.139, P = 0.025) and non‐diabetic patients (OR 2.097, 95% CI 1.093‐4.026, P = 0.026), while HbA1c was not significantly associated with adverse events occurrence . Interestingly a study by Okada et al, enrolling acute coronary syndrome patients who underwent stent implantation and subsequent intravascular ultrasounds after a 9‐month follow‐up, observed that a high GV was an independent determinant of increased lipid and decreased fibrous contents with larger plaque burden, suggesting glucose abnormalities as one of the important factors related to coronary plaque vulnerability .…”
Section: The Clinical Impact Of Gv On CV Complicationsmentioning
confidence: 72%
“…13 Furthermore, in a cohort of 237 patients with ST segment elevation MI undergoing PCI, a higher GV was demonstrated to be an independent prognostic factor for composite MACE during in-hospital and 30-day follow-up both for diabetic (OR 2.857, 95% CI 1.143-7.139, P = 0.025) and non-diabetic patients (OR 2.097, 95% CI 1.093-4.026, P = 0.026), while HbA1c was not significantly associated with adverse events occurrence. 65 Interestingly a study by Okada et al, enrolling acute coronary syndrome patients who underwent stent implantation and subsequent intravascular ultrasounds after a 9-month follow-up, observed that a high GV was an independent determinant of increased lipid and decreased fibrous contents with larger plaque burden, suggesting glucose abnormalities as one of the important factors related to coronary plaque vulnerability. 11 An association between GV, even though evaluated by SGBM, and major CV and cerebrovascular events was also demonstrated during a 30-day follow-up in 864 acute coronary syndrome patients (OR 1.97, 95% CI 1.32-6.86; P = 0.02).…”
Section: Pathophysiological Mechanisms Relating Gv and CV Complicatmentioning
confidence: 99%
“…The mean amplitude of glycemic excursion (MAGE) is the mean of blood glucose values exceeding one SD from the 24‐hour mean blood glucose and is used as an index of glycemic variability . According to the scientific literature, the value of MAGE in patients without DM are nearly 30 to 40 mg/dL, and the cutoff value of MAGE for cardiovascular events are considered nearly 60 to 70 mg/dL …”
Section: Introductionmentioning
confidence: 99%